2003
DOI: 10.1128/ec.2.5.1069-1075.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Catalase in the Microsporidian Nosema locustae : Implications for Microsporidian Metabolism and Genome Evolution

Abstract: Microsporidia constitute a group of extremely specialized intracellular parasites that infect virtually all animals. They are highly derived, reduced fungi that lack several features typical of other eukaryotes, including canonical mitochondria, flagella, and peroxisomes. Consistent with the absence of peroxisomes in microsporidia, the recently completed genome of the microsporidian Encephalitozoon cuniculi lacks a gene for catalase, the major enzymatic marker for the organelle. We show, however, that the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…In the extremely compacted genomes of microsporidia, however, it is possible that what is a minor force in "normal" genomes takes on a more substantial role, resulting in the greater degree of stability apparent between these two distantly related species. The absences of repetitive and mobile DNA in the genome further enhance this effect, although evidence for some repetitive DNA exists in A. locustae (14), and retroelements exist in V. corneae (39) and Spraguea lophii (22). If compaction has enhanced genome stability in microsporidia, then it has probably done so only at certain levels of organization.…”
Section: Comparative Genomics and The Impacts Of Genome Reduction In mentioning
confidence: 99%
See 1 more Smart Citation
“…In the extremely compacted genomes of microsporidia, however, it is possible that what is a minor force in "normal" genomes takes on a more substantial role, resulting in the greater degree of stability apparent between these two distantly related species. The absences of repetitive and mobile DNA in the genome further enhance this effect, although evidence for some repetitive DNA exists in A. locustae (14), and retroelements exist in V. corneae (39) and Spraguea lophii (22). If compaction has enhanced genome stability in microsporidia, then it has probably done so only at certain levels of organization.…”
Section: Comparative Genomics and The Impacts Of Genome Reduction In mentioning
confidence: 99%
“…However, these studies looked only at relatively short genomic fragments and did not provide clues to the influence of such elements in genome architecture. A. locustae (formerly Nosema locustae) (53, 54) is another microsporidian for which more-substantial genomic data have now been produced (13,14,51). A. locustae has been shown to be relatively distantly related to E. cuniculi (53,54); however, a random genome survey of 685 kbp showed that the two genomes have a good deal in common.…”
Section: Comparative Genomics and The Impacts Of Genome Reduction In mentioning
confidence: 99%
“…Alternatively, there may be large gene-poor regions of the genome that have not been sampled. The region around catalase (Fast et al 2003) could represent one such area since this 13,000 bp region only contains three genes (for a density of only 0.23 genes/Kbp -over four times lower than the average found in gene-rich areas). Lastly, it is also possible that most of the genome shares a high gene-density, but that more than one copy of some genes exist.…”
Section: Limited Variation In Gene Contentmentioning
confidence: 99%
“…Catalase converts hydrogen peroxide to water and hydrogen gas, and is a marker enzyme for peroxisomes, although it is also found in many prokaryotes in eukaryotes outside of the organelle. A. locustae has been shown to encode a catalase of the non-peroxisomal, group II variety that is functional and expressed in spores (Fast et al 2003). The gene is likely not ancestral to microsporidia, since it is not of fungal ancestry, but is instead derived from a proteobacterium by lateral gene transfer.…”
Section: Limited Variation In Gene Contentmentioning
confidence: 99%
“…The first cases of HGT in eukaryotes were associated with parasite evolution [21,22]. Whether through acquisition of antibiotic resistance, pathogenicity islands, or expanding to new metabolism [23] or host-specific environments [24], HGT is due in part to the fact that those genes that confer some evolutionary benefit are most likely to be found in other organisms already adapted to those circumstances [25]. [26] identified the source of the cholera outbreak in Haiti as a group of Nepalese peacekeeping troops.…”
mentioning
confidence: 99%